Pengaruh Brand Image, Brand Satisfaction dan Brand Trust terhadap Loyalitas Konsumen pada Suara Surabaya - Asyam Raeshard Noviar; Siti Ning Farida (J-MAS (Jurnal Manajemen dan Sains), 2022)
Suara Surabaya started from a radio station domiciled in the city of Surabaya, Suara Surabaya is a media company that belongs to the old generation, which is able to struggle to maintain its existence and continue to compete with new media that comes. One of the streaming media, namely YouTube and Spotify, which has skyrocketed in popularity since the beginning of their entry into the entertainment or entertainment industry. The research method used is a quantitative approach method. The source of data for this study was obtained from Suara Surabaya consumers in the Surabaya area, and based on the answers to the questionnaire that will be distributed by the researchers. The analysis technique in this study uses the Validity and Reliability Test. Then after that using Descriptive Analysis and Hypothesis Testing. The results of the F test in this study showed Fhitung of 32.264 and Ftabel of 3.09, so that the results of the calculation of Fhitung > Ftabel were 32.264 > 3.09. The t-test of the Brand Image variable shows the results of tcount > ttable of 2,554 > 1,985 with a significant value of 0.000. The results of Hypothesis Testing 1 Brand Image (X1) Brand Satisfaction (X2) and Brand Trust (X3) simultaneously significantly influence Surabaya Voice's Loyalty, Hypothesis 2 Brand Image (X1) partially significantly influences Surabaya Voice's Consumer Loyalty (Y) , Hypothesis 3 Variable Brand Satisfaction (X2) partially has a significant influence on Consumer Loyalty (Y) Suara Surabaya, Hypothesis 4 Variable Brand Trust (X3) partially has a significant influence on Consumer Loyalty (Y) Suara Surabaya.